Faktor-Faktor yang Berpengaruh pada Kesiapan Mahasiswa dalam Menghadapi Dunia Kerja di Era Digitalisasi - Wirawati, Ni Gusti Putu; Dwija Putri, I Gusti Ayu Made Asri (E-Jurnal Akuntansi; Vol 33 No 1 (2023), 2023)
This study aims to determine the effect of ethical competency, knowledge competency, capability competency, relationship competency, analysis competency, and intellectual performance on undergraduate accounting stundent’s readiness in fancing the era of digitazation.   Determination of the sample used is random sampling method . Data analysis technique that used is multiple linear regression analysis. The results of the study found that ethical competency, knowledge competency, capability competency, relationship competency, analysis competency,  and intellectual performance has positive effects on undergraduate accounting stundent’s readiness in fancing the era of digitazation. Keywords: Competency; Intellectual Performance; Readiness of Collage Stundent; Era of Digitazion